Magnetic/Magnetostrictive Properties Together with Resistivity and Corrosion Behaviors of CoFe2 and Its Composite with CoFe2N. Issue 7 (July 2017) - Geng, B.Q.; Ma, Y.Q.; Wang, M.; Ding, Z.L.; Song, W.H.; Zhao, B.C.
Abstract : The CoFe2 alloy (CF) was prepared by reducing CoFe2 O4 in the H2 ambient. Subsequently the CF sample was nitrided in the NH3 atmosphere to produce the composite of CoFe2 N and CoFe2 . The magnetostriction, thermal expansion, resistivity and corrosion resistance of CF sample and the nitrided sample (CFN) at 1000 °C were investigated. The saturation magnetostriction coefficiency λ s and thermal expansion coefficient α at 300 K for the nitrided CFN were 50 ppm and 10 ppm/K, respectively, approximately equal to those for the CF sample. However, compared with CF, CFN presents a decrease in temperature coefficient Rλ (300 K) of magnetostriction by ~11%. The smaller resistivity and improved corrosion resistance in the H2 SO4 solution may expand the applications of the CoFe2 in the fields needing lower resistivity or in the acidic environment.